On the linkage of momentum and reversal – evidence from the G7 stock markets - Daniel Hofmann; Karl Ludwig Keiber; Adalbert Luczak (Journal of Economics and Finance, 2024)
Abstract This paper studies the linkage of momentum and reversal in the G7 stock markets. We confirm Conrad and Yavuz's (Rev Financ 21(2):555–581, 2017 ) finding that momentum is not linked to subsequent return reversal in the US stock market. In the stock markets of the remaining G7 countries, our results object the decoupling of momentum and return reversal. In these stock markets, the two return anomalies are linked to each other. In particular, momentum is followed by return reversal in the stock markets of Germany, the UK, Japan, Canada, France, and Italy. These observations obtain for momentum portfolios which are made up of different risk profiles with respect to size and book-to-market ratio. Our results hold true both in raw returns and in risk-adjusted returns.
Additional information: G11;G15;G40
Keywords: 330; Momentum; Return reversal; Linkage; International stock markets